Development Of E-Module In Subject Basic Computer Graphics In Class X – DKV SMK NEGERI 11 Malang To Increase Student Interest In Learning - Faradillah Aditya Purnomo; Faizatul Amalia; Satrio Hadi Wijoyo (Faculty of Computer Science (FILKOM) Brawijaya University, 2025)
Learning can run well with an interest in learning for students. Based on this, researchers found problems at SMK NEGERI 11 MALANG. One of the problems encountered was the low interest in learning for class X – DKV students in the Basic Computer Graphics subject. Therefore, the Basic Computer Graphic E-module is here to provide a solution to this problem. The development of this E- module uses the ADDIE method which consists of five stages (analyze, design, development, implementation and evaluation). Data collection was carried out using structured interview techniques, literature studies and filling out questionnaires (pre-E-module and post-E-module). Tests carried out include testing the feasibility of the E-module and testing the increase in student learning interest. Questionnaire calculations were carried out using a Likert scale, with a scale of 1-4. Based on the tests carried out by the E-module, the results of the eligibility percentage were 70% (Eligible) by material experts, 79.16% (Decent) by media experts, 88.3% (Very Feasible) by media eligibility experts and 84.19% (Very Worthy) by users. Furthermore, the percentage of students' interest in learning obtained an increase of 66.65% with a percentage of interest in learning before the E-module of 12.7% (Very Poor) and after using the E-module of 79.35% (Good). So it can be concluded that the E-module can be considered feasible and able to increase student learning interest.